2013
DOI: 10.1186/1754-6834-6-31
|View full text |Cite
|
Sign up to set email alerts
|

Single-step ethanol production from lignocellulose using novel extremely thermophilic bacteria

Abstract: BackgroundConsolidated bioprocessing (CBP) of lignocellulosic biomass to ethanol using thermophilic bacteria provides a promising solution for efficient lignocellulose conversion without the need for additional cellulolytic enzymes. Most studies on the thermophilic CBP concentrate on co-cultivation of the thermophilic cellulolytic bacterium Clostridium thermocellum with non-cellulolytic thermophilic anaerobes at temperatures of 55°C-60°C.ResultsWe have specifically screened for cellulolytic bacteria growing at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 36 publications
(64 reference statements)
1
62
0
Order By: Relevance
“…This yield obtained can by compared with the yield by other wild type bacteria. Svetlitchnyi et al [54] reported maximum ethanol yield of 3.5 g/l from the wild type bacterium Caldicellulosiruptor DIB 004C. Sato et al [55] reported ethanol production of 4 g/l by wild type Clostridum thermocellum strain I-1-B and an improved 23.6 g/l ethanol by the same strain when grown in optimized medium.…”
Section: Discussionmentioning
confidence: 99%
“…This yield obtained can by compared with the yield by other wild type bacteria. Svetlitchnyi et al [54] reported maximum ethanol yield of 3.5 g/l from the wild type bacterium Caldicellulosiruptor DIB 004C. Sato et al [55] reported ethanol production of 4 g/l by wild type Clostridum thermocellum strain I-1-B and an improved 23.6 g/l ethanol by the same strain when grown in optimized medium.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few microorganisms able to grow at such temperatures are able to generate ethanol from sugar (8)(9)(10), and no bacterium growing above 70°C produces an alcohol other than ethanol. In addition, no member of the domain Archaea is known to produce any alcohol as a major product, regardless of growth temperature.…”
mentioning
confidence: 99%
“…Examples of strictly anaerobic thermophiles that have been studied for biofuel production are Clostridium thermocellum (14,15), several Caldicellulosiruptor spp. (16)(17)(18), as well as Thermoanaerobacterium spp. and Thermoanaerobacter spp.…”
mentioning
confidence: 99%